Comparison of Electrical Quantity Characteristics with or without Neural Point on Load Side of 1400MVA Nuclear Power Turbo-generator. Issue 1 (20th January 2019) - Lv, Pin; Ge, Baojun; Lin, Peng; Zhao, Hongsen
Abstract: At the time being, the discussion on comparison of the current and voltage characteristics between with and without neural point on load side about the large nuclear turbo-generator is not sufficient. To investigate the current and voltage characteristics in large nuclear power turbo-generator with alteration of load impendence coefficient with or without neural point on load side, in this paper a 1400MVA nuclear power turbo-generator is selected as a research object and its two-dimensional finite element model is established. By no-load and short-circuit characteristics, the comparison of the armature current and voltage between the two-dimensional finite element method and the experimental value shows preferable consistency and the accuracy of the simulation model is verified. With or without neutral point on load side the finite element simulation model is developed to achieve three-phase current and voltage characteristics with alteration of load impendence coefficient respectively. Then on this basis, the symmetrical method and Fourier transform are harnessed to process the simulation date. Moreover, the positive sequence voltage characteristics, as well as the negative sequence voltage characteristics, is presented. The concrete conclusion in this paper has precious theoretical and practical meanings for over- and light-voltage protection in nuclear power turbo-generators as well.